Insecticidal Efficiency of Some Pesticides Against Spodoptera Frugiperda (J.E. Smith) (Noctuidae: Lepidoptera) Under Laboratory Conditions - Moustafa M.S. Bakry; Mohamed A. Gad (Universitas Andalas, 2023)
The